Nutrition and Chronic Diseases among Makkah Visitors (Global Journal of Medical Research, 2019)
Chronic conditions are thought to affect ahigh number of the general population of pilgrims and Umrah visitors. With a little planning and preparation, people with chronic illnesses should have safe and enjoyable Umrah rituals. The study aimed to characterize the association between chronic diseases and dietary regimens among Umrah visitors. Data collection questionnaire designed for recording of the most expected diseases among Umrah visitors. The results showed that out of 401 Umrah visitors suffering from chronic diseases, 80.8% of them were on medication. The most disease was diabetes mellitus (41.4%) followed by blood hypertension (31.9%), chronic respiratory disease (18.5%) and chronic heart diseases (6.5%). Also, 44.9% of them were doing Umrah for the second time of their life, and 59.6 % of the patients had a special food program. Statistically, there was a significant association between age and the type of chronic disease (p-value 0.05).
Keywords: makkah; umrah visitors; travelers; chronic diseases; nutrition